Climatic conditions for grapevine cultivation in Boa Vista, Roraima, Brazil = Aptidão climática para o cultivo da videira em Boa Vista, Roraima - Marco Antônio Fonseca Conceição (Agro@mbiente On-line, 2014)
Grapevine plants have been grown in different tropical regions of Brazil. In the state of Roraima, this culture was introduced commercially in 2005 in Boa Vista. Unlike temperate regions, tropical regions present thermal conditions for grape production throughout the year. To evaluate the climatic characteristics on different periods of the year, it can be used different indices. The objective of this study was to characterize climate suitability of Boa Vista, Roraima, Brazil, for grapevine cultivation at different months of the year. For climate classification it was used the Geoviticulture Multicriteria Climatic Classification System (CCM), which is composed by three indices: Heliothermal (IH), Cool Night (IF), and Drought (IS). It was also used the Zuluaga Index (IZ), to assess the risk of incidence of fungal diseases on the vine, especially in relation to the incidence of downy mildew (Plasmopara viticola), one of the main grapevine diseases in humid regions. Based on the evaluated indices, it was found that the most favorable period for grape production goes from October to March because of the lower values of rainfall. During the other months, it can be employed branch pruning without fruit production, as occurs in other tropical locations of Brazil. =A videira tem sido cultivada em diferentes regiões tropicais do Brasil. No estado de Roraima, ela foi implantada comercialmente em 2005 em Boa Vista. Ao contrário das regiões de clima temperado, as regiões tropicais apresentam condições térmicas para a produção de uvas durante o ano inteiro. Para se avaliar as características climáticas dos diferentes períodos do ano pode-se recorrer a diversos índices. Objetivou-se, com o presente trabalho, avaliar a aptidão climática de Boa Vista, Roraima, para o cultivo da videira, considerando-se diferentes períodos de produção ao longo do ano. Na caracterização climática, foi utilizado o Sistema de Classificação Climática Multicritérios Geovitícola (CCM), que é composto por três índices: Heliotérmico (IH), de Frio Noturno (IF) e de Seca (IS). Também foi empregado o Índice de Zuluaga (IZ), para avaliar os riscos de incidência de doenças fúngicas da videira, especialmente em relação à incidência de míldio (Plasmopara viticola), uma das principais doenças em regiões úmidas. Com base nos índices avaliados, verificou-se que o período mais favorável para a produção de uvas vai de outubro a março, por apresentar menores valores de pluviometria. Nos outros meses, podem ser realizadas podas de formação de ramos, sem a produção de frutos, como já ocorre em outras localidades tropicais do Brasil.